Analisis Media Program Tayangan Kartun Berdasarkan Pedoman P3SPS - Ma'amun, Muhammud Amin; Wijayani, Qoniah Nur (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
The aim of this research is to explore, describe and analyze forms of violations and their sanctions. The application of sanctions for violations that occur is based on the 2012 KPI Broadcasting Behavior Guidelines and Program Standards (P3SPS). This research method is descriptive and prescriptive, calculating and aims to collect information about the condition of a symptom, especially the condition of the symptom. depending on the situation at the time the research is carried out. The research location is the East Kalimantan KPID office. Data collection was carried out through observation, interviews and notes. The study was moderated by 11 people, including the East Kalimantan KPID coordinator, psychology teacher, science communication teacher, as well as parents and children who watched the film Shaun the Sheep. Data analysis was carried out using data reduction methods, data presentation and drawing conclusions. From this examination, violations were found in the MNC TV program "Shaun the Sheep" which aired on July 21 2017, including violations related to programs with sexual connotations, child protection, and classification of broadcast programs. This program influences changes in children's attitudes and behavior while watching, especially in terms of imitation ability. P3 and SPS should be guidelines during/during the production of television programs so that they can present quality, healthy and useful viewing